Factors influencing behavior and their implications to personal relationships in professional teaching - Fonacier, Josefa B. (Education quarterly.)
The purpose of this paper is to review and analyze several literature on human behavior in organization in order to help others achieve their goals, their joy of living, with a minimum effort and maximum satisfaction both on their part and the people around them. The problem at hand is to understand and analyze why people behave differently from the accepted norms of behavior. Why do teachers sometimes feel apathetic, indifferent and discontented? Why do they feel like quitting their teaching job? What are the factors that influence such behavior?